Capitalizing on Language Learners' Individuality From Premise to Practice - Gregersen, Tammy; MacIntyre, Peter D. (Second Language Acquisition, 2014)
This book closes the gap between theory and classroom application by capitalizing on learners’ individuality in second or foreign language learning. The book examines the existing literature and theoretical underpinnings of each of the most prominent learner characteristics including anxiety, beliefs, cognitive abilities, motivation, strategies, styles and willingness to communicate. This strong foundation, coupled with the wide variety of activities that are suggested at the end of each chapter, arms the reader with ideas to conquer the problems created by negative affect and to capitalize on positive, facilitative emotions. The tasks are unrestricted by language and can be modified for use with technology, emergent learners and large classes, making this book a useful resource for both in-service teachers and pre-service teachers in university language teacher education programs